ENGLISH PHRASAL VERBS AND THEIR TRANSLATION INTO RUSSIAN AND UZBEK (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the English lexical system, the phrasal verb is known as the subject and component. The increase in interest in phrase verbs is associated with their active use in speech and writing by native English speakers. It is necessary to understand the semantic meaning of idioms in order to continue the conversation and develop fluent communication skills. Curricula, methods and tools for successfully teaching verb phrases are given in the article with a modern analytical view.